Global logistics for dummies - Erb, John J.; James, Sarah R. (--For dummies., 2017)
Deliver global disaster and relief logistics support -Explore global manufacturing and distribution logistics -Provide logistics services for foreign customers Operate in a global logistics environment There's no need to jump into the global logistics market unprepared. This hands-on guide is your parachute, offering the expert, actionable guidance you need to ensure your journey is a smooth one from start to finish. Covering everything you'll encounter in this exciting - but often intimidating - business environment, this is the essential resource you want to have close at hand. Inside .-Make a case for going global -Involve the whole business -Discern cultural differences -Figure out best practices -Deal with disaster relief -Recover from losses/theft -Benefit from others' experiences.